Une histoire de la réception de Flaubert en Hongrie - Krisztina Horváth (Flaubert: Revue Critique et Génétique)
The study of the history of Flaubert’s reception in Hungary follows a number of key questions. What are the key milestones in the critical reception of Flaubert’s works, and can we speak of a periodisation? Is it (still) true that Flaubert is reduced to Madame Bovary in the Hungarian canon of world literature? How is Flaubert treated in some major Hungarian critical texts and literary histories? What are the major translations and retranslations? One of the key issues under review is whether there has been a theoretical turning point in the history of this reception.